Pengaruh Beban Kerja dan Kompensasi terhadap Kinerja Pegawai di Dinas Kearsipan dan Perpustakaan Daerah Kabupaten Kendal - Ippiyah Ippiyah; Heri Usodo (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
This study aims to analyze the effect of workload and compensation on employee performance at the Regional Archives and Library Office of Kendal Regency. The rising number of library visitors has increased employees' workload, while disbursement of employee compensation has often been delayed, creating a gap between job demands and rewards that may affect performance. A quantitative approach was applied using a saturated sampling technique, involving all 75 employees of the office as respondents. Data were collected through questionnaires measured with a five-point Likert scale and analyzed using multiple linear regression with the assistance of SPSS 26. The results show that workload has a positive and significant effect on employee performance, with a t-value of 5.872 greater than the t-table value of 1.993 and a significance value of 0.000. Compensation also has a positive and significant effect on performance, indicated by a t-value of 3.090 greater than 1.993 and a significance value of 0.003. Simultaneously, workload and compensation significantly affect employee performance, with an F-value of 101.998 and an R-square of 0.739, meaning both variables jointly explain 73.9% of the variance in performance. These findings imply that balanced workload distribution and fair, timely compensation are essential for improving employee performance in public library and archival institutions.